Peranan Kepala Desa sebagai Mediator dalam Penyelesaian Sengketa Harta Waris di Desa Sempol - Andila, Yoni Bunga (Res Judicata, 2026)
The Village Head, based on Article 26 Paragraph (4) letter (l) of the Village Law, is tasked with resolving community disputes in his/her village. This research aims to analyze the role of the Village Head as a Mediator, how the Village Head as a Mediator faces obstacles, and the division of roles between the Village Head as a Mediator in resolving inheritance disputes in Sempol Village. The research method used in this research is empirical legal research method. This research shows that: First, the role of the Village Head in the mediation process to resolve inheritance disputes in Sempol Village is considered not optimal, such as the absence of mediation minutes and written agreements containing the agreement of the parties. Second, the Village Head faces obstacles in the mediation process by first identifying the obstacles and then resolving them according to the characteristics of each obstacle, but it is still not optimal because the Village Head has not been equipped with Mediator knowledge. Third, there was no division of Mediator roles between the Sempol Village Head and the Pagak Village Head. All of the shortcomings in the mediation process could be avoided if: 1) The Village Head actively equips himself with mediation knowledge. 2) The government facilitates the Village Head with training and certification of Mediators, to strengthen the competence of the Village Head, improve community justice, reduce the burden on the courts and provide clear and legal guidelines for dispute resolution in practice.